Women in time a character analysis of the female characters in the video game Chrono Cross - Feliciano, Ana Marie Czarmaine A., author (College of Arts and Letters, University of the Philippines Diliman, 2012)
Video games have rapidly begun to replace books and other media of literature as a source of entertainment and recreation for teens and young adults. This study analyzes a video game using the techniques of Narratology and Characterization, as well as Sara Mill's Feminist Stylistics in order to reveal how women are portrayed in the game. The video game analyzed in the study is Chrono Cross, which tells the story of a young boy's travel across two alternate realities to discover the truth behind his existence, and the truth behind the two parallel dimensions. Along the way, he encounters 44 playable characters, each with his or her personal tale and motivations. In order to determine how women are portrayed in the video game, ten of the female playable characters are analyzed. The study uses Manfred Jahn's concept of indirect presentations to determine the details of characterization to be collected. The study examines the 1) female character's situation at the time of recruitment, including her history, appearance, name and her back story; 2) dialogues of the female character; 3) weapon choices and skills of the character in question; 4) rationale or reason that the character is joining the party; and 5) relationships that the character develops throughout the game. The study reveals that several traits recur in the characterization of the female characters, and that these traits are founded on the characters/role stereotypes and on the idea of Schemata regarding the behavior of women. The analysis is founded on the ideas of the four main threads of feminism: Liberal feminism, Materialist feminism, Cultural feminism and Postmodern feminism. Due to the contradictions between and among these given threads, the portrayal of women in the game can be seen as either empowering or disempowering, depending on which lens of feminism is used.